KAJIAN SARANA SANITASI DASAR PONDOK PESANTREN AL - FATTAH DI DESA BANJARSARI KECAMATAN BUDURAN KABUPATEN SIDOARJO - Eka Anggraini; Imam Thohari; Nur Haidah (Poltekkes Kemenkes Surabaya, 2013)
Basic sanitation in Islamic Boarding School is very necessary to paid attention because of themain problem in Islamic Boarding School as basic sanitation aspects is ineligible. These basicsanitation included clean water supply, trash fill means, wastewater outlet means, latrine meansthat can be produced various diseasessuch as, diarrhea, dermatitis, and inhalation congestion.This research as descriptive research with cross sectional approach purposed to recognize onbasic sanitation means AI-Fattah Islamic Boarding School in Banjarsari village Buduran DistrictSidoarjo Regency, where performed assessmenttoward the conditions of infrastructure such asclean water supply, trash fill means, wastewater outlet means, latrine means. Data collectingdone with observation and interview. Data taken then analyzed descriptively.The result of the research of assessment toward basic sanitation means Al-Fattah IslamicBoarding School included clean water supply gain score 257 (71,3%), trash fill means gain 70(50%), wastewater outlet means gain score 66 (47,2%), latrine means gain score 272 (75,5%).Suggested in order to improving the cleaning frequency in basic sanitation facilities routinely tokeep their cleanliness.Keywords : Basic Sanitation Islamic Boarding School